Developing an interactive multimedia learning courseware about animal discovery for children / Maznah Bujah - Bujah, Maznah (2004)
This multimedia interactive project is focused on building and developing a multimedia interactive courseware for animal discovery, in particular, for children recognize and learn about animal. This Animal Discovery introduces children to a variety of animals in a nonpencil format that makes learning fun. The project's component is to develop courseware that goes beyond the simple text and pictures multimedia so often found (i.e., has some sound pedagogical principles behind it and involves interactivity). I have chosen to use the multimedia learning courseware as my delivery platform.